2020
DOI: 10.1017/ipm.2020.19
|View full text |Cite
|
Sign up to set email alerts
|

Using a television programme as a tool to increase perceived awareness of mental health and well-being – findings from ‘Our Mental Health’ survey – ERRATUM

Abstract: Reference McTernan, N., Ryan F., Williamson E., Chambers D., & Arensman E. (n.d.). Using a television programme as a tool to increase perceived awareness of mental health and well-beingfindings from'OurMental Health' survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…The survey found that 94% of respondents expressed their belief that the documentary had a positive impact, underscoring the importance and potential of media, especially mainstream televisions, as a tool for influencing attitudes and awareness surrounding mental health. Furthermore, the survey revealed that 91% of participants perceived the documentary as encouraging for young people to open up and talk to someone if they are experiencing mental health difficulties, and that viewers had a 5% higher level of intention to seek help than non-viewers, further showcasing the influence this television program had (Ryan, Williamson, Chambers, Arensman, & McTernan, 2020). This proves that, given the opportunity for freedom of speech to grow and spread positive information without any sorts of restriction, or in the case where it was being used for good, huge societal progress could be made.…”
Section: Resultsmentioning
confidence: 99%
“…The survey found that 94% of respondents expressed their belief that the documentary had a positive impact, underscoring the importance and potential of media, especially mainstream televisions, as a tool for influencing attitudes and awareness surrounding mental health. Furthermore, the survey revealed that 91% of participants perceived the documentary as encouraging for young people to open up and talk to someone if they are experiencing mental health difficulties, and that viewers had a 5% higher level of intention to seek help than non-viewers, further showcasing the influence this television program had (Ryan, Williamson, Chambers, Arensman, & McTernan, 2020). This proves that, given the opportunity for freedom of speech to grow and spread positive information without any sorts of restriction, or in the case where it was being used for good, huge societal progress could be made.…”
Section: Resultsmentioning
confidence: 99%
“…The immersive power of television serials through emotional engagement and connection provides older adults a satisfying life and well-being, which could extend successful ageing. The potential elements of television, such as its narrative style and characters, create an immersive state where viewers can forget the real world and have a positive influence on emotional well-being (Hammond et al, 2023; McTernan et al, 2023). Whether knowingly or unknowingly, engaging with television serials can help people forget their real-life problems and escape from their worries.…”
Section: Discussionmentioning
confidence: 99%